Human but Not Laboratory Borna Disease Virus Inhibits Proliferation and Induces Apoptosis in Human Oligodendrocytes In Vitro. - Dan Li (Public Library of Science (PLoS), 2013)
Borna disease virus (BDV) is a neurotropic virus that produces neuropsychiatric dysfunction in a wide range of warm-blooded species. Several studies have associated BDV with human psychiatric illness, but the findings remain controversial. Although oligodendrocytes are a major glial component of brain white matter and play a pivotal role in neuronal cell function, BDV's effects on human oligodendrocytes have not been clarified. Here, the effects of two BDV strains, Hu-H1 (isolated from a bipolar patient) and Strain V (a laboratory strain), on the proliferation and apoptosis of human oligodendrocytes were investigated. Three experimental cell lines were constructed: Hu-H1-infected oligodendroglioma (Hu-H1) cells, Strain V-infected oligodendroglioma (Strain V) cells, and non-infected oligodendroglioma (control) cells. BDV infection was assayed by BDV nucleoprotein (p40) immunofluorescence, cell proliferation was assayed by Cell Counting Kit-8 (CCK8), and cell cycle phases and apoptosis were assayed by flow cytometry. Expressions of the apoptosis-related proteins Bax and Bcl-2 were measured by Western blotting. p40 expression was confirmed in Hu-H1 and Strain V on and after day three post-infection. Strain V cells showed significantly greater cellular proliferation than Hu-H1 cells on and after day three post-infection. In Hu-H1 cells, Bax and Bcl-2 expression were significantly increased and decreased, respectively, on and after day three post-infection. In contrast, in Strain V cells, Bax and Bcl-2 expression were significantly decreased and increased, respectively, on and after day three post-infection. In conclusion, Hu-H1 inhibits cellular proliferation and promotes apoptosis in human oligodendrocytes via Bax upregulation and Bcl-2 downregulation. In contrast, Strain V promotes cellular proliferation and inhibits apoptosis in human oligodendrocytes via Bax downregulation and Bcl-2 upregulation. The effects of the Hu-H1 strain (isolated from a bipolar patient) are opposite from those of Strain V (a laboratory strain), thereby providing a proof of authenticity for both.